1993
DOI: 10.2172/10173279
|View full text |Cite
|
Sign up to set email alerts
|

Extension of the M-D model for treating stress drops in salt

Abstract: The multimechanism deformation model for the creep deformation of salt is extended to treat the response of salt to imposed stress drops. Stress drop tests produce a very distinctive behavior where both reversible elastic strain and reversible time dependent strain occur. These transient strains are negative compared to the positive transient strains produced by the normal creep workhardening and recovery processes. A simple micromechanical evolutionary process is defined to account for the accumulation of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 4 publications
0
8
0
Order By: Relevance
“…The phenomenological analysis method, the viscoelastic plasticity model, and the empirical formula are the main methods used for constructing the rock salt constitutive relation (Munson et al, 1993). In this study, the foundational model was defined by the classical creep constitutive model obtained by the empirical formula method.…”
Section: Salt Rock Creep Constitutive Relationmentioning
confidence: 99%
“…The phenomenological analysis method, the viscoelastic plasticity model, and the empirical formula are the main methods used for constructing the rock salt constitutive relation (Munson et al, 1993). In this study, the foundational model was defined by the classical creep constitutive model obtained by the empirical formula method.…”
Section: Salt Rock Creep Constitutive Relationmentioning
confidence: 99%
“…t creep < 0). This phenomenon is observed in the laboratory during uniaxial multi-step creep tests and is referred to as "inverse creep" (Van Sambeek, 1993;Hunsche, 1991;Munson et al, 1996;Charpentier et al, 1999). The effects of transient inverse creep in a cavern have been described by Hugout (1988) In this paragraph, the origin of time is the day when cavern leaching is completed.…”
Section: Transient Creepmentioning
confidence: 99%
“…is process may be individually controlled by one mechanism under some specific conditions; however, it is controlled by several mechanisms in parallel in the vast majority of cases. Munson et al [83] summarised the microcreep deformation mechanisms of salt rock under different conditions. e results showed that the creep deformation of salt rock is mainly controlled by the dislocation slip mechanism under high-stress conditions, while it is controlled by dislocation climb mechanism under low stress and high temperature conditions.…”
Section: Microscopic Creep Deformation Mechanism Of Salt Rockmentioning
confidence: 99%